Analysis of e-learning implementation in adult learning (andragogy) - Indah Namira Sari; Dinn Wahyudin; Rusman Rusman (Inovasi Kurikulum, 2024)
E-learning has relevance to be applied to adult learning as independent learners. This research aims to analyze the effectiveness of e-learning in adult learning (andragogy). In the context of adult learning based on continuous e-learning, there are significant changes in the objectives and content of teaching, social roles, forms, and nature of communication between teachers and students, based on e-learning. The research method uses a literature study of 77 articles found and analyzed based on the steps used. The research results showed that articles regarding e-learning in adult learning were found on the topics "learning outcomes" in higher education, "implementation according to plan" in job training institutions, "application in work practice" in job training institutions, satisfaction, and efficiency. Based on these results, it can also be seen that measuring the effectiveness of e-learning in adult learning mostly uses quantitative and qualitative methods. Meanwhile, although the mixed method exists, it is not as big as the other two methods. Then, the factors supporting the effectiveness of e-learning in adult learning were found in the number of selected articles, namely those related to the quality of teachers/students/lecturers, infrastructure, quality of teaching materials, and quality of learning strategies.   Abstrak E-learning memiliki relevansi untuk diterapkan pada pembelajaran orang dewasa sebagai pebelajar mandiri. Tujuan penelitian ini untuk menganalisis efektivitas e-learning pada pembelajaran orang dewasa (andragogi). Dalam konteks pembelajaran orang dewasa pembelajaran berbasis e-learning secara berkelanjutan, maka terdapat perubahan signifikan dalam tujuan dan isi pengajaran, peran sosial, bentuk dan sifat komunikasi antara guru dan peserta didik, berbasis e-learning. Metode penelitian menggunakan studi literature terhadap 77 artikel yang ditemukan dan dilah berdasarkan langkah-langkah yang digunakan sebagai metode. Hasil penelitian menunjukkan bahwa artikel yang mengenai e-learning dalam pembelajaran orang dewasa ditemukan pada topik “hasil pembelajaran” pada pendidikan tinggi, “pelaksanaan sesuai dengan rencana” pada lembaga pelatihan kerja, “aplikasi dalam praktik kerja” pada lembaga pelatihan kerja, kepuasan, dan efisiensi. Berdasarkan hasil tersebut juga dapat dilihat bahwa pengukuran efektivitas e-learning pada pembelajaran orang dewasa sebagian besar menggunakan metode kuantitatif dan kualitatif. Sementara untuk metode campuran meskipun ada tetapi tidak sebesar kedua metode lainnya. Kemudian ditemukan faktor-faktor pendukung efektivitas e-learning pada pembelajaran orang dewasa dari jumlah artikel yang terseleksi yakni berkaitan dengan kualitas guru/pegajar/dosen, sarana prasarana, kualitas bahan ajar, dan kualitas strategi pembelajaran. Kata Kunci: andragogi; efektivitas e-learning; e-learning; studi literatur